Gerakan sosial pemuda Gunggungan Lor dalam melestarikan budaya perawatan jenazah ala Ahlussunnah wal Jama’ah - Ainol, Ainol; Adawiyah, Rofiatul; Kartika, Diva; Aisah, Siti; Kulsum, Umi; Nur’aini, Zulfiyah Puteri (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2025)
: Not many Muslim communities have the courage to care for corpses. Only a handful of people dare to wash, shroud and enter the grave during the burial process for the deceased. This phenomenon cannot be separated from the existence of dead people who are still mythical as tuyul embryos or child kuntils. As a result, many teenagers do not master the skills of caring for corpses and their specifications during the shroud process. In fact, it is on the shoulders of teenagers to preserve the culture of shrouding corpses. If this phenomenon is allowed to continue, there will be a cadre crisis in preserving the culture of caring for corpses in the style of ahlusunnah wal congregation, so it is feared that there will be a scarcity of young Muslim cadres who are experts in shrouding corpses. It is in this dimension that this research offers significance. The main aim is to describe the concern of Gunggungan Lor teenagers in raising funds when a death occurs in their community, continuing to dig the grave, bathe them, give prayers to finish the funeral. The method used is Accet Base Community Development which is packaged in the form of Community Service. The ABCD approach is a critical approach within the scope of development based on the strengths and assets owned by the community. This approach places great emphasis on community independence and the establishment of rules. The ABCD approach focuses on the assets you want to develop. The results of the research show the creation of an increase in understanding in caring for corpses ala ahlus sunnah wal jamaah for the youth of Gungungan Lor; the realization of skills and abilities in bathing, shrouding, praying and burying the dead.